If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -20 = 31 + 3x Solving -20 = 31 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -20 + -3x = 31 + 3x + -3x Combine like terms: 3x + -3x = 0 -20 + -3x = 31 + 0 -20 + -3x = 31 Add '20' to each side of the equation. -20 + 20 + -3x = 31 + 20 Combine like terms: -20 + 20 = 0 0 + -3x = 31 + 20 -3x = 31 + 20 Combine like terms: 31 + 20 = 51 -3x = 51 Divide each side by '-3'. x = -17 Simplifying x = -17
| 6b-12b+4c+6d= | | 2(x-5)3x=20 | | x+5x-7x+3-x=48 | | 1-(3y+3)=-8 | | -5q-10=-6q | | 4q-3y=27 | | 19-16-17h=-7-18h | | 1-3y+3=-8 | | -38(15x)+28(24x)=(75-75)+(-608+98) | | 5(3x-4)-3=5(x-2)+37 | | 8k=9+7k | | 10m+4=74mis | | -7-2x=2 | | -8d+6=20-10d+18 | | -9m=9-10m | | 24=8(x+2) | | -x+4+4=13 | | 2x(x-3)=18x^2-7x | | -608+98= | | -3(s+17)=-15 | | 9x-126=2x+49 | | -5(1+3x)=70 | | 19.9u+19.89=17.46-4.42+19.4u | | -38(-15x)+28(24x)= | | 6=-x-x | | 17j+-16j=19 | | 4x+264=8x | | 4+26=-3(3x-10) | | 2(2x-7)-2=2(x-2)+2 | | 1/2x+4=30 | | -4q-18q+1=-19q+19 | | -19u-(-15u)=4 |